Analisis Implementasi Algoritma Penanganan Kegawat Pra Rumah Sakit Oleh Masyarakat sebagai First Responder di Surakarta - Widodo Widodo; Sumardino Sumardino (Poltekkes Kemenkes Surakarta, 2020)
Abstract Background: Between 2006-2015, there were reported at least 6270 disasters affecting 5 continents. Of the total disasters, there were at least 8,197.66 people died, 70,597 survival nd damage to the economic sector was around 1,989,866,263 dollars. The safety of the victims are very dependent on various factors, therefore collaboration of the whole community is needed in providing first aid at the scene before getting help from the health setting. The purpose for this study is to describe the understanding of prehospital emergency management algorithms for the community as the first respondent in Surakarta. Methods: This study uses an pre experimental research design with the Pre-Test-Post Test Group design without control group with the subject of people of Surakarta City after recruited using consecutive sampling techniques and 222 respondent were finally recruited. After following pretest, respondents received training about the implementation of the firtst aid algorythm and post-test was delivered at the end. The variable in this study is the community's ability in providing first aid during emergency in the community. Result: A questionner was used to meassure knowledge before and after following training. Wilcoxon Match Pair test was used to compare the data from pre-test and post-test. The majority of subjects have good knowledge and increased knowledge after following training pertaining to be first responders. Conclusion: Training and simulation are essential in order to increase and maintain first responders capacity in providing aid before referring to health care setting. In addition, community needs to continue to be given socialization and understanding of the existence of PSC 119 so that the first aid that has been given optimally will get maximum further assistance.